2003
DOI: 10.1210/jc.2002-021905
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-Related Apoptosis-Inducing Ligand (TRAIL), TRAIL Receptors, and the Soluble Receptor Osteoprotegerin in Human Gestational Membranes and Amniotic Fluid during Pregnancy and Labor at Term and Preterm

Abstract: We have studied TNF-related apoptosis-inducing ligand (TRAIL) and its membrane-bound (R1-R4) and soluble receptors [osteoprotegerin (OPG)] in gestational membranes to assess their significance in preterm parturition and premature rupture of membranes (PROM). TRAIL was detected by ELISA in extracts of term choriodecidual (but not amnion) tissues and explant-conditioned media. Concentrations of OPG (determined using ELISA) in gestational membranes were 20- to 50-fold greater than those of TRAIL. Median OPG conce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 34 publications
2
40
0
1
Order By: Relevance
“…OPG has received particular attention; its levels are stable during pregnancy and only rise at term, when they double in parallel with an apparently paradoxical increase in bone resorption (38,39). The rapid post partum fall in OPG suggests a placental origin, which has been corroborated by the finding of a high concentration of OPG in placental membranes (40). The circulating levels of RANKL have been investigated in studies that have reported parallel changes to those of OPG (41,42).…”
Section: Other Regulatorsmentioning
confidence: 99%
“…OPG has received particular attention; its levels are stable during pregnancy and only rise at term, when they double in parallel with an apparently paradoxical increase in bone resorption (38,39). The rapid post partum fall in OPG suggests a placental origin, which has been corroborated by the finding of a high concentration of OPG in placental membranes (40). The circulating levels of RANKL have been investigated in studies that have reported parallel changes to those of OPG (41,42).…”
Section: Other Regulatorsmentioning
confidence: 99%
“…The same lines could not be killed by recombinant TRAIL, indicating that, at least in trophoblast tumor cell lines, DcR1 (TRAIL-R3) may protect against apoptosis. More recently, Lonergan et al (2003) have reported that osteoprotegerin, a soluble receptor for TRAIL, as well as the two TRAIL decoy receptors, TRAIL-R3 and -R4, are high in gestational membranes and may protect against the proapoptotic effects of locally produced TRAIL. Thus, all three receptors may be important.…”
Section: Protection From Endogenous Trailmentioning
confidence: 99%
“…The Csf 2 null mutation increased expression of Cd24a, which encodes a mucin-like cell adhesion molecule, CD24, that shows reduced placental expression in preeclampsia [63]. Tnfrsf11b, which was downregulated in Csf 2 null mutant placentae, encodes osteoprotegerin, a cytokine that may protect gestational tissues from apoptosis [64]. Another gene strongly downregulated by the Csf 2 null mutation was Lilrb4, which encodes a leukocyte immunoglobulin-like receptor, CD85K, that is implicated in the signaling pathway through which placental HLA-G exerts immunosuppressive effects in T lymphocytes [65].…”
Section: Placental Development In Csf2-deficient Mice 217mentioning
confidence: 99%